Urban ‘tourism exploration space’: the example of Łódź - Liszewski, Stanisław (Turyzm/Tourism, 2009)
The author refers to the concept of ‘tourism space’ published earlier, and confronts this notion with a definition of ‘urban space’, bearing in mind that both these ‘spaces’ are subspaces of general ‘geographical space’. Assuming that each is distinguished on the basis of differing criteria, the author believes that the tourism function which gives rise to ‘tourism space’ can develop within ‘urban space’. Further on, the formulation of a precise definition of urban ‘tourism exploration space’ is focused on, which is understood as a personal space of created in the discovery of a city. The conclusion includes three case studies of urban ‘tourism exploration space’ in Łódź: Bidermann family properties, Piotrkowska courtyards and the ‘Green Ring of Tradition and Culture’.